Acheron - Kenyon, Sherrilyn 1965- (New York St. Martin's Paperbacks, 2009)
Determined to solve an ancient mystery, a woman undertakes a forbidden quest that pits her against Dark-Hunters leader and proud god Acheron Parthenopaeus, with whom she joins forces when ancient guardians and old enemies threaten both of them.
Keywords: Gods -- Fiction; Enemies -- Fiction; Imaginary wars and battles -- Fiction; Fantasy fiction; Romantic suspense fiction